Comparative Analysis of Complete Chloroplast Genomes and Phylogenetic Relationships in Medicinally Important Pantropical Genus Bauhinia s.s. (Leguminosae) from Southern Africa and Eastern Asia - (:unkn) unknown (My University, 2025)
Bauhinia s.s. belongs to the Cercidoideae subfamily, located at the base of the Leguminosae family. It displays a variety of growth habits and morphologies, and is widely utilized as both ornamental and medicinal plants globally. The objective of this research is to uncover chloroplast genomes of species from Eastern Asia and Southern Africa, thereby advancing our understanding of the diversity within this genus. This study sequenced Bauhinia purpurea, Bauhinia brachycarpa var. microphylla, Bauhinia variegata var. candida, Bauhinia galpinii, and Bauhinia monandra using the Illumina platform and conducted the construction of phylogenetic trees as well as the estimation of divergence times. Compared to Asian species, the IR regions of African species underwent a contraction of approximately 100–400 bp. The phylogenetic analysis indicated that Asian and African species clustered into two distinct clades, with high support. The divergence of Bauhinia s.s. species occurred in the late Paleocene, and the rps18 and cemA genes were under positive selection. Six hypervariable regions were screened for evolutionary studies and the super-barcode data were used for species delimitation. The results revealed certain differences between African and Asian species in their chloroplast genomes of Bauhinia species.
Keywords: African Research